2001
DOI: 10.1021/ma010048c
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle Neutron Scattering from Single Arm Labeled Polybutadiene Star Polymers in Dilute Solution

Abstract: Dilute cyclohexane solutions of polybutadiene star polymers with 3, 4, 8, and 12 arms wherein one arm is perdeuterated have been investigated by small-angle neutron scattering. The scattering cross sections obtained showed a characteristic peak at finite values of the scattering vector, Q. This maximum is not a structure factor arising from intermolecular interactions but is intrinsic to the scattering law of star molecules with one arm of a different isotopic composition to the other arms. The theoretical sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This is not unexpected since the Zimm-Stockmayer expression was developed for swollen Gaussian chains. In the case of short-arm star polymers the high polymer segment densities cause congestion leading to stiffening of the star arms close to the core 22,53,[60][61][62] (see inset illustration in Figure 6). Hence, the deviation to higher ratios at lower molecular weight stars.…”
Section: Resultsmentioning
confidence: 99%
“…This is not unexpected since the Zimm-Stockmayer expression was developed for swollen Gaussian chains. In the case of short-arm star polymers the high polymer segment densities cause congestion leading to stiffening of the star arms close to the core 22,53,[60][61][62] (see inset illustration in Figure 6). Hence, the deviation to higher ratios at lower molecular weight stars.…”
Section: Resultsmentioning
confidence: 99%
“…The dependence of the radii of gyration of a single arm on the number of arms was studied by small angle neutron scattering by Hutchings et al in a system of single arm deuterated stars 57. The authors found a linear increase in the radius of gyration of one arm with increasing number of arms.…”
Section: Resultsmentioning
confidence: 99%
“…The most notable difference between the tethering process for the two architectures was that the surface attachment density of four-arm PEO-NH 2 was about 4−5 times greater than that of linear PEO-NH 2 at all times during the tethering process, indicating a higher tethering rate for the four-arm PEO-NH 2 . In the tethering process, diffusion of the polymer molecule to the surface rather than its chemical reaction with the surface is the rate-determining step. ,,,, Since rate of diffusion through solvent is inversely proportional to R g , four-arm PEO-NH 2 , with R g = 2.63 nm, would diffuse only 18% faster than linear PEO-NH 2 , with R g = 3.10 nm . Thus, the effect of polymer architecture, i.e., four-arm vs linear, on diffusion through the solvent is relatively minor, and the explanation of the dramatic increase in rate and surface attachment density must lie elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…In the tethering process, diffusion of the polymer molecule to the surface rather than its chemical reaction with the surface is the rate-determining step. 1,2,5,6,10 Since rate of diffusion through solvent is inversely proportional to R g , four-arm PEO-NH 2 , with R g ) 2.63 nm, 11 would diffuse only 18% faster than linear PEO-NH 2 , with R g ) 3.10 nm. 12 Thus, the effect of polymer architecture, † University of Kentucky.…”
Section: Resultsmentioning
confidence: 99%